Negative active material and preparation method thereof, negative pole piece, secondary battery and device
By forming a porous carbon layer and depositing silicon particles on the surface of the expansion graphite, the problem of low circulation stability of the existing negative active materials is solved, and the high ratio and magnification performance improvement is achieved.
Patent Information
- Application Number
- CN202310909413.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2023-07-24
- Publication Date
- 2025-01-24
- Estimated Expiration
- 2043-07-24
AI Technical Summary
The existing silicon-based carbon-based composite negative electrode active materials have a low level in terms of cycle stability, resulting in poor performance of secondary batteries.
By forming a porous carbon layer on the surface of the expansion graphite, and the porous carbon layer of the porous carbon layer is deposited in the porous carbon layer, silicon particles are deposited to form a negative active material to improve the uniform distribution of silicon particles and the cycle stability of the negative electrode material.
This method not only improves the cycle stability of the negative active material, but also enhances its specific capacity and rate performance, making it suitable for high-capacity power battery applications.
Smart Images

Figure CN119361615A_ABST
Abstract
Description
Technical Field
[0001] The present application belongs to the field of battery technology, and specifically relates to a negative electrode active material and a preparation method thereof, a negative electrode plate, a secondary battery and a device. Background Art
[0002] The statements herein merely provide background information related to the present application and do not necessarily constitute prior art.
[0003] Secondary batteries are widely used in various consumer electronic products and electric vehicles due to their outstanding features such as light weight, no pollution, and no memory effect. As the market demand for high-capacity power batteries grows, negative electrode materials with high theoretical specific capacity such as silicon-based materials are being developed.
[0004] However, although silicon-based materials have high theoretical specific capacity, they swell severely during charging and have low first discharge efficiency. Therefore, in order to obtain negative electrode materials with more balanced performance, it is often necessary to compound silicon-based materials with carbon-based materials as negative electrode active materials. However, the cycle stability of silicon-based and carbon-based composite negative electrode active materials is still at a low level. Summary of the invention
[0005] Based on this, it is necessary to provide a negative electrode active material and a preparation method thereof, a negative electrode plate, a secondary battery and a device that can improve cycle stability.
[0006] In a first aspect of the present application, a negative electrode active material is provided, comprising expanded graphite, a porous carbon layer and silicon particles, wherein the expanded graphite comprises a plurality of graphite layers, the porous carbon layer is at least distributed on an interlayer surface of one of the graphite layers, and the silicon particles are at least distributed in the pores of the porous carbon of the porous carbon layer.
[0007] Without wishing to be limited to any theory, the above-mentioned negative electrode active material of the present application is prepared by pre-forming a porous carbon layer on the interlayer surface of expanded graphite, and then distributing silicon particles at least in the pores of the porous carbon in the porous carbon layer. The pores of the porous carbon provide storage space for the uniform deposition of silicon particles, so that the silicon particles can be evenly dispersed between the layers of the expanded graphite, which is not only conducive to the high load of silicon particles, but also the lamellar structure of the expanded graphite is also conducive to the structural enhancement and conductivity improvement of the internal negative electrode active material, and also provides space for the expansion of silicon particles during the cycle, thereby improving its stability during the cycle.
[0008] The traditional method of directly depositing silicon particles in expanded graphite to prepare negative electrode active materials is, on the one hand, difficult to achieve a high loading of silicon particles. On the other hand, the disordered filling state of silicon particles inside the expanded graphite and the uneven grain distribution of silicon particles will lead to uneven volume distribution of the prepared negative electrode active materials during the cycle, and cause uneven distribution and excessive consumption of active lithium, which in turn leads to poor cycle stability of the negative electrode active materials.
[0009] The above-mentioned negative electrode active material of the present application retains the advantages of expanded graphite in enhancing mechanical strength and conductivity, and optimizes the distribution and filling method of silicon particles, thereby obtaining a negative electrode active material with both higher specific capacity and higher cycle stability.
[0010] In any embodiment of the present application, the porous carbon layer covers the surface of at least one of the graphite layers; optionally, the porous carbon layer covers the surface of each of the graphite layers.
[0011] In any embodiment of the present application, the expanded graphite is oxidized expanded graphite;
[0012] Optionally, the oxygen-containing groups in the expanded graphite include at least one of hydroxyl groups, epoxy groups and carboxyl groups.
[0013] In any embodiment of the present application, at least one of the following conditions is met:
[0014] (1a) The mass ratio of the porous carbon layer to the expanded graphite is (0.1-20):1, and can be optionally (4-16):1;
[0015] (1b) The thickness of the porous carbon layer is 0.05 to 20 μm, and can be 0.2 to 10 μm;
[0016] (1c) The BET specific surface area of the porous carbon layer is 40 to 1500 m 2 / g, optional: 600~1500m 2 / g;
[0017] (1d) The average pore size of the porous carbon layer is 0.1 to 40 nm;
[0018] (1e) The porous carbon layer is doped with nitrogen atoms; optionally, the mass content of the nitrogen atoms relative to the porous carbon layer is 0.1% to 20%.
[0019] In any embodiment of the present application, at least one of the following conditions is met:
[0020] (2a) The mass ratio of the silicon particles to the expanded graphite is (0.08-20):1, and can be optionally (3-18):1;
[0021] (2b) The macroscopic average particle size of the silicon particles is 0.05 to 30 nm;
[0022] (2c) The mass ratio of the silicon particles to the porous carbon layer is (0.7-12):1, and can be (0.7-1.5):1;
[0023] (2d) In the negative electrode active material, the mass content of the silicon particles is 6% to 65%;
[0024] (2e) The expanded graphite is oxidized expanded graphite; optionally, the oxygen-containing groups in the expanded graphite include at least one of hydroxyl groups, epoxy groups and carboxyl groups; optionally, the mass content of the oxygen-containing groups in the expanded graphite is 0.5% to 38%.
[0025] In any embodiment of the present application, the negative electrode active material further comprises a coating layer, and the coating layer is coated on at least a portion of the outer surface of the expanded graphite;
[0026] Optionally, the coating layer comprises a carbon material;
[0027] Optionally, the mass content of the coating layer in the negative electrode active material is 0.2% to 3%;
[0028] Optionally, the coating layer has a thickness of 0.5 to 200 nm.
[0029] In a second aspect of the present application, a method for preparing any of the above-mentioned negative electrode active materials is provided, comprising the following steps:
[0030] Mixing expanded graphite with a carbon source solution and performing a hydrothermal reaction, and then calcining a solid product of the hydrothermal reaction to obtain an intermediate product; the intermediate product includes expanded graphite and a porous carbon layer distributed on the surface of a graphite layer in the expanded graphite; and
[0031] Silicon particles are formed in the pores of the porous carbon of the intermediate product.
[0032] In any embodiment of the present application, at least one of the following conditions is met:
[0033] (3a) the carbon source in the carbon source solution comprises at least one of glucose, asphalt, sucrose and phenolic resin;
[0034] (3b) the mass ratio of the carbon source in the carbon source solution to the expanded graphite is (1-200):1;
[0035] (3c) A nitrogen source is further added to the hydrothermal reaction; optionally, the nitrogen source comprises at least one of pyrrole, melamine and acetonitrile;
[0036] (3d) the hydrothermal reaction temperature is 80 to 280° C. and the time is 0.5 to 5 h;
[0037] (3e) The calcination conditions include: calcining at 400-1000° C. for 1-5 hours.
[0038] In any embodiment of the present application, the step of forming silicon particles in the pores of the porous carbon of the intermediate product comprises the following steps:
[0039] Passing silane and reducing gas into the intermediate product, and performing chemical vapor deposition under a protective atmosphere;
[0040] Optionally, the silane includes at least one of monosilane and disilane;
[0041] Optionally, the temperature of the chemical vapor deposition is 400-1000° C.;
[0042] Optionally, the chemical vapor deposition time is 1 to 5 hours.
[0043] In any embodiment of the present application, a gas raw material is introduced into the product obtained by chemical vapor deposition to perform chemical vapor deposition, and the gas raw material includes at least one of ethylene, acetylene and propylene;
[0044] Optionally, the temperature of the chemical vapor deposition is 600-1200° C.;
[0045] Optionally, the chemical vapor deposition time is 1 to 5 hours.
[0046] In any embodiment of the present application, the expanded graphite is oxidized expanded graphite; the preparation method further comprises the step of preparing the oxidized expanded graphite, comprising the following steps:
[0047] After the expanded graphite is soaked in an acid solution and washed to neutrality, oxidized expanded graphite is obtained;
[0048] Optionally, the acid solution includes at least one of HNO3 and H2SO4.
[0049] In a third aspect of the present application, a negative electrode plate is provided, wherein the negative electrode plate comprises any one of the negative electrode active materials described above.
[0050] In a fourth aspect of the present application, a secondary battery is provided, comprising the above-mentioned negative electrode plate.
[0051] In a fifth aspect of the present application, there is provided an electrical device comprising the above-mentioned secondary battery.
[0052] The details of one or more embodiments of the present application are set forth in the following drawings and description. Other features, objects, and advantages of the present application will become apparent from the description, drawings, and claims. BRIEF DESCRIPTION OF THE DRAWINGS
[0053] In order to more clearly illustrate the technical solution of the present application, the following is a brief introduction to the drawings used in the present application. Obviously, the drawings described below are only some embodiments of the present application, and for ordinary technicians in this field, other drawings can be obtained based on the drawings without creative work.
[0054] Figure 1 is a schematic structural diagram of a negative electrode active material according to an embodiment of the present application;
[0055] Figure 2 is a schematic structural diagram of a negative electrode active material according to another embodiment of the present application;
[0056] Figure 3 is a schematic diagram of a battery cell according to an embodiment of the present application;
[0057] Figure 4 yes Figure 3 An exploded view of a battery cell according to an embodiment of the present application is shown;
[0058] Figure 5 is a schematic diagram of a battery module according to an embodiment of the present application;
[0059] Figure 6 A schematic diagram of a battery pack according to an embodiment of the present application;
[0060] Figure 7 for Figure 6 An exploded view of a battery pack according to an embodiment of the present application is shown;
[0061] Figure 8 is a schematic diagram of an electrical device using a secondary battery according to an embodiment of the present application as a power source;
[0062] Description of reference numerals:
[0063] 1. Battery cell; 11. Shell; 12. Electrode assembly; 13. Cover plate; 2. Battery pack; 21. Upper case; 22. Lower case; 3. Battery module; 4. Electrical device; 5. Negative electrode active material; 511. Graphite layer; 52. Porous carbon layer; 53. Coating layer. DETAILED DESCRIPTION
[0064] Hereinafter, the embodiments of the present application are specifically disclosed in detail with appropriate reference to the accompanying drawings. However, there may be cases where unnecessary detailed descriptions are omitted. For example, there may be cases where detailed descriptions of well-known matters and repeated descriptions of actually the same structures are omitted. This is to avoid the following description from becoming unnecessarily lengthy and to facilitate the understanding of those skilled in the art. In addition, the drawings and the following description are provided for those skilled in the art to fully understand the present application and are not intended to limit the subject matter described in the claims.
[0065] "Scope" disclosed in the present application is limited in the form of lower limit and upper limit, and a given range is limited by selecting a lower limit and an upper limit, and the selected lower limit and upper limit define the boundary of a special range. The scope limited in this way can be including end values or not including end values, and can be arbitrarily combined, that is, any lower limit can be combined with any upper limit to form a scope. For example, if the scope of 60-120 and 80-110 is listed for a specific parameter, it is understood that the scope of 60-110 and 80-120 is also expected. In addition, if the minimum range values 1 and 2 are listed, and if the maximum range values 3, 4 and 5 are listed, the following scope can be all expected: 1-3, 1-4, 1-5, 2-3, 2-4 and 2-5. In the present application, unless otherwise specified, the numerical range "ab" represents the abbreviation of any real number combination between a and b, wherein a and b are real numbers. For example, the numerical range "0-5" means that all real numbers between "0-5" are listed in this document, and "0-5" is just an abbreviation of these numerical combinations. In addition, when a parameter is expressed as an integer ≥ 2, it is equivalent to disclosing that the parameter is, for example, an integer of 2, 3, 4, 5, 6, 7, 8, 9, 10, 11, 12, etc.
[0066] Unless otherwise specified, all embodiments and optional embodiments of the present application can be combined with each other to form a new technical solution.
[0067] If there is no special explanation, all steps of the present application can be performed sequentially or randomly, preferably sequentially. For example, the method includes steps (a) and (b), which means that the method may include steps (a) and (b) performed sequentially, or may include steps (b) and (a) performed sequentially. For example, the method may further include step (c), which means that step (c) may be added to the method in any order. For example, the method may include steps (a), (b) and (c), or may include steps (a), (c) and (b), or may include steps (c), (a) and (b), etc.
[0068] In this application, in the open technical features or technical solutions described by the words "contain", "include", "include", etc., if there is no other explanation, additional members other than the listed members are not excluded, and it can be regarded as providing both closed features or solutions consisting of the listed members and open features or solutions including additional members in addition to the listed members. For example, A includes a1, a2 and a3. If there is no other explanation, it may also include other members or may not include additional members. It can be regarded as providing both the feature or solution of "A consists of a1, a2 and a3" and the feature or solution of "A includes not only a1, a2 and a3, but also other members".
[0069] Unless otherwise specified, the terms used in this application have the commonly known meanings generally understood by those skilled in the art. Unless otherwise specified, the numerical values of the various parameters mentioned in this application can be measured using various measurement methods commonly used in the art (for example, they can be tested according to the methods given in the examples of this application).
[0070] Secondary battery
[0071] A secondary battery is a battery that can be recharged to activate the active materials after being discharged and continue to be used.
[0072] Generally, a secondary battery includes a positive electrode sheet, a negative electrode sheet, and an electrolyte. During the battery charging and discharging process, active ions are embedded and extracted back and forth between the positive electrode sheet and the negative electrode sheet. It can be understood that the active ions originate from the positive electrode active material of the positive electrode sheet.
[0073] Negative electrode
[0074] The negative electrode plate generally includes a negative electrode current collector and a negative electrode film layer disposed on the negative electrode current collector, wherein the negative electrode film layer includes a negative electrode active material.
[0075] An embodiment of the present application provides a negative electrode active material, including expanded graphite, a porous carbon layer and silicon particles. The expanded graphite includes a plurality of graphite layers. The porous carbon layer is at least distributed on the interlayer surface of a graphite layer, and the silicon particles are at least distributed in the pores of the porous carbon of the porous carbon layer.
[0076] Expanded Graphite (EG) is a loose, porous, worm-like substance obtained by intercalating, washing, drying, and high-temperature expansion of natural graphite flakes. Like graphite, expanded graphite has a layered structure with multiple graphite layers. In each graphite layer, the carbon atoms are sp 2 Hybridization, each carbon atom is bonded to three other carbon atoms by covalent bonds to form a hexagonal network structure; between graphite layers, they are bonded by intermolecular forces.
[0077] In some of the embodiments, the structure of the negative electrode active material can be confirmed by scanning transmission electron microscopy.
[0078] It can be understood that the graphite layers of the expanded graphite include a graphite layer located in the middle and a graphite layer located in the outer layer according to their positions. Among them, the outward surface of the graphite layer located in the outer layer is considered to be exposed, and it is not located between the layers, that is, the outer surface of the expanded graphite. The inward surface of the graphite layer located in the outer layer and the two surfaces of the graphite layer located in the middle are considered to be interlayer surfaces, that is, "interlayer surfaces of graphite layers".
[0079] It can be understood that the porous carbon layer is distributed not only on the interlayer surface of the graphite layer, but also on the outer surface of the expanded graphite.
[0080] Without wishing to be limited to any theory, the above-mentioned negative electrode active material of the present application is prepared by pre-forming a porous carbon layer on the interlayer surface of expanded graphite, and then distributing silicon particles at least in the pores of the porous carbon in the porous carbon layer. The pores of the porous carbon provide storage space for the uniform deposition of silicon particles, so that the silicon particles can be evenly dispersed between the layers of the expanded graphite, which is not only conducive to the high load of silicon particles, but also the lamellar structure of the expanded graphite is also conducive to the structural enhancement and conductivity improvement of the internal negative electrode active material, and also provides space for the expansion of silicon particles during the cycle, thereby improving its stability during the cycle.
[0081] The traditional method of directly depositing silicon particles in expanded graphite to prepare negative electrode active materials is, on the one hand, difficult to achieve a high loading of silicon particles. On the other hand, the disordered filling state of silicon particles inside the expanded graphite and the uneven grain distribution of silicon particles will lead to uneven volume distribution of the prepared negative electrode active materials during the cycle, and cause uneven distribution and excessive consumption of active lithium, which in turn leads to poor cycle stability of the negative electrode active materials.
[0082] The above-mentioned negative electrode active material of the present application retains the advantages of expanded graphite in enhancing mechanical strength and conductivity, and optimizes the distribution and filling method of silicon particles, thereby obtaining a negative electrode active material with both higher specific capacity and higher cycle stability.
[0083] Furthermore, the negative electrode active material of the present application is applied to a secondary battery, which also improves the rate performance of the secondary battery.
[0084] In some embodiments, the porous carbon layer covers the surface of at least one graphite layer.
[0085] Optionally, the porous carbon layer covers the surface of part of the expanded graphite or each graphite layer.
[0086] In some embodiments, the expanded graphite is oxidized expanded graphite. It is understandable that the oxidized expanded graphite contains oxygen-containing groups, and optionally, the oxygen-containing groups in the expanded graphite include at least one of hydroxyl, epoxy and carboxyl groups. Hydroxyl, epoxy and carboxyl groups are introduced between the graphite layers of the expanded graphite, providing polar groups for the adsorption of carbon sources during the preparation of the porous carbon layer, so that the carbon source can be more strongly attached to the graphite layer through these oxygen-containing groups, and the porous carbon is oriented and uniformly grown along the thickness direction on the surface of the graphite layer.
[0087] Further, the mass content of oxygen-containing groups in the expanded graphite is 0.5% to 38%, optionally 3% to 37.5%, more optionally 4% to 37.5%, or 17% to 37.5%. As an example, the mass content of oxygen-containing groups in the expanded graphite can be 0.5%, 1%, 2%, 3%, 4%, 5%, 10%, 15%, 17%, 18%, 20%, 25%, 30%, 35%, 37.5%, 38%.
[0088] In some embodiments, the mass ratio of the porous carbon layer to the expanded graphite is (0.1-20): 1. Controlling the mass ratio of the porous carbon layer to the expanded graphite within the above range can provide sufficient attachment and storage space for the subsequent deposition of silicon particles, which is conducive to the uniform dispersion of silicon particles between the layers of the expanded graphite and a higher content loading.
[0089] As an example, the mass ratio of the porous carbon layer to the expanded graphite may be 0.1: 1, 0.2: 1, 0.5: 1, 1: 1, 2: 1, 3: 1, 4: 1, 5: 1, 6: 1, 7: 1, 8: 1, 9: 1, 10: 1, 11: 1, 12: 1, 13: 1, 14: 1, 15: 1, 16: 1, 17: 1, 18: 1, 19: 1, 20: 1. Optionally, the mass ratio of the porous carbon layer to the expanded graphite may be a range consisting of any two of the above point values, for example (4-16): 1.
[0090] It can be understood that the "silicon particles" herein include but are not limited to pure silicon particles, and may also be silicon-containing particles such as silicon-oxygen particles and silicon-carbon particles. In some embodiments, the mass ratio of silicon particles to the porous carbon layer is (0.7-12):1. As an example, the mass ratio of silicon particles to the porous carbon layer may be 0.7:1, 0.8:1, 0.9:1, 1:1, 1.2:1, 1.5:1, 2:1, 5:1, 6:1, 7:1, 10:1, 12:1. The mass ratio of silicon particles to the porous carbon layer may be (0.7-1.5):1, and more preferably (0.7-1.2):1. Further controlling the range of the mass ratio of silicon particles to the porous carbon layer can allow as many silicon particles as possible to be deposited in the pores of the porous carbon layer, rather than excessively deposited on the surface of the porous carbon layer, so as to improve the stability of the negative electrode active material, thereby facilitating the improvement of the cycle stability and rate performance of the battery to which it is applied.
[0091] In some embodiments, the thickness of the porous carbon layer is 0.05 to 20 μm. The thickness of the porous carbon layer is controlled within this range to obtain a porous carbon layer with a relatively stable structure. In some specific examples, the porous carbon layer can be formed by in-situ growth of a carbon source along the thickness direction of the surface of the graphite layer under hydrothermal conditions.
[0092] It is understood that the thickness of the porous carbon layer can be controlled by the mass ratio of the carbon source to the expanded graphite, the temperature and time of the hydrothermal reaction. The adhesion firmness of the porous carbon layer on the surface of the graphite layer is related to the mass content of the oxygen-containing groups in the expanded graphite.
[0093] As an example, the thickness of the porous carbon layer may be 0.05 μm, 0.1 μm, 0.15 μm, 0.2 μm, 0.5 μm, 1 μm, 2 μm, 3 μm, 4 μm, 5 μm, 6 μm, 7 μm, 8 μm, 9 μm, 10 μm, 12 μm, 14 μm, 16 μm, 18 μm, 20 μm. Optionally, the thickness of the porous carbon layer may be a range consisting of any two of the above point values, for example, 0.2 to 10 μm.
[0094] In some embodiments, the BET specific surface area of the porous carbon layer is 40 to 1500 m 2 / g, optional: 600~1500m 2 / g. BET specific surface area refers to the specific surface area obtained by BET adsorption test method. As an example, the BET specific surface area of the porous carbon layer can be 40m 2 / g、100m 2 / g, 160m 2 / g, 170m 2 / g, 200m 2 / g、300m 2 / g, 400m 2 / g、500m2 / g、600m 2 / g、700m 2 / g, 750m 2 / g、800m 2 / g, 850m 2 / g、900m 2 / g, 950m 2 / g、1000m 2 / g、1100m 2 / g、1200m 2 / g、1300m 2 / g、1400m 2 / g、1500m 2 / g, or a range consisting of any two of the above point values.
[0095] In some embodiments, the average pore size of the porous carbon layer is 0.1 to 40 nm. The average pore size is determined by magnifying the surface of the material through a microscope photograph or the like, calculating the number of pores per unit length (e.g., when the pore size is approximately in the range of 0.1 to 2 nm, the unit length is 10 nm; or when the pore size is approximately in the range of 2 to 40 nm, the unit length is 100 nm) as the number of cells, and then calculating the average pore size by the following equation: average pore size = unit length / number of cells.
[0096] In some embodiments, the porous carbon layer is doped with nitrogen atoms, which can increase the defect concentration in the porous carbon layer, thereby increasing the lithium ion transmission rate of the negative electrode active material and further improving the rate performance of the secondary battery to which it is applied.
[0097] Further, the mass content of nitrogen atoms relative to the porous carbon layer is 0.1% to 20%. As an example, the mass content of nitrogen atoms relative to the porous carbon layer can be 0.1%, 0.2%, 0.5%, 1%, 2%, 4%, 5%, 7%, 10%, 12%, 14%, 16%, 18%, 20%. The mass content of nitrogen atoms relative to the porous carbon layer can be obtained by elemental analysis.
[0098] In some embodiments, the mass ratio of silicon particles to expanded graphite is (0.08-20): 1, and can be (3-18): 1. As an example, the mass ratio of silicon particles to expanded graphite is 0.08: 1, 0.2: 1, 0.5: 1, 0.7: 1, 1: 1, 2: 1, 5: 1, 6: 1, 7: 1, 8: 1, 10: 1, 11: 1, 12: 1, 13: 1, 14: 1, 15: 1, 16: 1, 18: 1, 20: 1, 22: 1, or a range consisting of any two of the above point values.
[0099] In some embodiments, the macroscopic average particle size of the silicon particles is 0.05-30 nm.
[0100] The macroscopic average particle size of the silicon particles can be obtained by performing XRD testing on the above-mentioned negative electrode active material and calculating it using the Scherrer formula based on the characteristic peaks of the silicon particles therein.
[0101] In some embodiments, the silicon particles include but are not limited to silicon particles, and may also include at least one of silicon carbon particles, silicon nitrogen particles, etc. In a specific example, the silicon particles are pure silicon particles.
[0102] In some embodiments, in the negative electrode active material, the mass content of silicon particles is 6% to 65%; optionally 6% to 50%, 10% to 50%, or 35% to 50%. As an example, the mass content of silicon particles can be 6%, 10%, 15%, 20%, 30%, 35%, 38%, 40%, 45%, 48%, 50%, 55%, 60%, 62%, 65%. The mass content of silicon particles in the above negative electrode active material can be obtained by ICP analysis.
[0103] In some embodiments, in the negative electrode active material, the mass content of expanded graphite is 2% to 85%. As an example, the mass content of expanded graphite can be 2%, 5%, 6%, 7%, 10%, 20%, 30%, 35%, 40%, 50%, 55%, 60%, 70%, 80%. In the negative electrode active material, the mass content of expanded graphite can be obtained by the following method: the negative electrode active material is fully soaked in DMC (dimethyl carbonate) for 5 hours, and then crushed by ion polishing. The powder obtained by crushing is subjected to XRD test to obtain the diffraction peak of the crystal peak with graphite structure, and the mass content of expanded graphite can be calculated by XRD internal standard method.
[0104] In some embodiments, the negative electrode active material further comprises a coating layer. The coating layer is coated on at least a portion of the outer surface of the expanded graphite. The structure of the negative electrode active material having the coating layer can also be confirmed by scanning transmission electron microscopy.
[0105] Further, the coating layer includes a carbon material. As an example, the coating layer may be a carbon material layer, such as an amorphous carbon layer.
[0106] Furthermore, the mass content of the coating layer in the negative electrode active material is 0.2% to 3%. As an example, the mass content of the coating layer in the negative electrode active material may be 0.2%, 0.5%, 1%, 1.5%, 2%, 2.5%, or 3%.
[0107] Furthermore, the coating layer has a thickness of 0.5 to 200 nm.
[0108] In such Figure 1 In the example shown, the negative electrode active material includes expanded graphite, a porous carbon layer 52 and silicon particles (not shown). The expanded graphite includes a plurality of graphite layers 511, the porous carbon layer 52 is at least distributed on the interlayer surface of one graphite layer 511, and the silicon particles are at least distributed in the porous carbon pores of the porous carbon layer 52. Specifically, the porous carbon layer 52 covers the surface of each graphite layer 511.
[0109] In such Figure 2 In the example shown, Figure 1 The difference shown is that it further includes a coating layer 53, which is coated on the outer surface of the expanded graphite; the coating layer 53 can be a continuous coating or a coating on a part of the surface.
[0110] On the other hand, the present application also provides a method for preparing the above-mentioned negative electrode active material, comprising the following steps S20 to S40.
[0111] S20, mixing the expanded graphite with the carbon source solution and performing a hydrothermal reaction, and then calcining the solid product of the hydrothermal reaction to obtain an intermediate product.
[0112] The intermediate product includes expanded graphite and a porous carbon layer distributed on the surface of a graphite layer in the expanded graphite.
[0113] In some embodiments, the expanded graphite is oxidized expanded graphite. Before step S20, the preparation method further includes a step of preparing oxidized expanded graphite, including the following step S10.
[0114] S10, soaking the expanded graphite in an acid solution and washing it until it becomes neutral to obtain oxidized expanded graphite.
[0115] Further, the acid solution includes at least one of HNO3 and H2SO4.
[0116] As an example, the acid solution is a mixture of concentrated nitric acid and concentrated sulfuric acid, with the volume ratio of the two being 1:1.
[0117] It can be understood that the degree of oxidation can be controlled by controlling the immersion time and the concentration of the acid solution in step S10.
[0118] In some embodiments, the carbon source in the carbon source solution includes at least one of glucose, asphalt, sucrose and phenolic resin.
[0119] In some embodiments, the mass ratio of the carbon source in the carbon source solution to the expanded graphite is (1-200): 1. It is understood that the mass ratio of the porous carbon layer to the expanded graphite can be controlled by controlling the mass ratio of the carbon source to the expanded graphite.
[0120] In some embodiments, a nitrogen source is also added to the hydrothermal reaction, so that nitrogen atoms are doped into the porous carbon layer.
[0121] Further, the nitrogen source includes at least one of pyrrole, melamine and acetonitrile. Further, the mass ratio of the nitrogen source to the expanded graphite is (0.02-20):100; optionally (0.1-20):100. It is understood that the mass content of nitrogen atoms in the porous carbon layer can be regulated by regulating the mass ratio of the nitrogen source to the expanded graphite.
[0122] In some embodiments, the temperature of the hydrothermal reaction is 80 to 280°C, and the time is 0.5 to 5 hours. As an example, the temperature of the hydrothermal reaction may be 80°C, 100°C, 120°C, 150°C, 160°C, 180°C, 200°C, 240°C, 260°C, 280°C, and the time may be 0.5h, 1h, 2h, 3h, 4h, 5h. Further, the temperature of the hydrothermal reaction is 150 to 240°C, and the time is 1h to 3h.
[0123] In some embodiments, the calcination conditions include: calcination at 400-1000° C. for 1-5 h. As an example, the calcination temperature may be 400° C., 500° C., 600° C., 700° C., 800° C., 900° C., 1000° C.; and the calcination time may be 1 h, 2 h, 3 h, 4 h, 5 h.
[0124] Furthermore, the calcination atmosphere may be an inert gas, nitrogen, air or vacuum atmosphere.
[0125] S40. Silicon particles are formed in the pores of the porous carbon of the intermediate product.
[0126] In some embodiments, S40 uses a chemical vapor deposition process; specifically, silane and a reducing gas are introduced into the intermediate product, and chemical vapor deposition is performed under a protective atmosphere, so that the silane is reduced to form silicon particles under the action of the reducing gas.
[0127] Further, in S40, the temperature of chemical vapor deposition is 400-1000° C. Further, in S40, the time of chemical vapor deposition is 1-5 hours.
[0128] As an example, in S40, the temperature of chemical vapor deposition may be 400°C, 500°C, 600°C, 700°C, 800°C, 900°C, or 1000°C; and the time of chemical vapor deposition may be 1 h, 2 h, 3 h, 4 h, or 5 h.
[0129] Further, the silane includes at least one of monosilane and disilane.
[0130] Further, the reducing gas includes acetylene. Further, the volume ratio of the reducing gas to silane is (0.02-1):1, and as an example, it can be 0.02:1, 0.05:1, 0.1:1, 0.5:1, 1:1. The reducing gas mainly plays the role of reducing silane to form silicon particles. Since the content of the reducing gas is smaller than that of silane, carbon particles are basically not generated, and carbon coating can be performed in the subsequent step S50.
[0131] Furthermore, in S40, a protective gas may be introduced as a carrier gas, and the protective gas may include at least one of an inert gas and nitrogen.
[0132] In some of the embodiments, after S40, a step of coating the product obtained in S40 may be further included, including step S50.
[0133] S50, introducing a gas raw material into the product obtained by the chemical vapor deposition in S40 to perform chemical vapor deposition, wherein the gas raw material includes at least one of ethylene, acetylene and propylene.
[0134] In this way, carbon is formed by thermal cracking of the gaseous raw material under chemical vapor deposition conditions.
[0135] Further, the temperature of the chemical vapor deposition in S50 is 600-1200° C. Further, in S50, the time of the chemical vapor deposition is 1-5 hours.
[0136] As an example, in S50, the temperature of chemical vapor deposition may be 600°C, 700°C, 800°C, 900°C, 1000°C, 1100°C, or 1200°C; and the time of chemical vapor deposition may be 1 h, 2 h, 3 h, 4 h, or 5 h.
[0137] As an example, the negative electrode current collector has two surfaces opposite to each other in its thickness direction, and the negative electrode film layer is disposed on any one or both of the two opposite surfaces of the negative electrode current collector.
[0138] In some embodiments, the negative electrode current collector may be a metal foil or a composite current collector. For example, as the metal foil, a copper foil may be used. The composite current collector may include a polymer material base layer and a metal layer formed on at least one surface of the polymer material substrate. The composite current collector may be formed by forming a metal material on a polymer material substrate. Among them, the metal material includes but is not limited to at least one of copper, copper alloy, nickel, nickel alloy, titanium, titanium alloy, silver and silver alloy; the polymer material substrate includes but is not limited to at least one of polypropylene (PP), polyethylene terephthalate (PET), polybutylene terephthalate (PBT), polystyrene (PS), and polyethylene (PE).
[0139] In some embodiments, the negative electrode film layer may contain, in addition to the negative electrode active material, a negative electrode active material for a battery known in the art. As an example, the negative electrode active material may also include at least one of the following materials: artificial graphite, natural graphite, soft carbon, hard carbon, silicon-based materials, tin-based materials, lithium titanate, etc. The silicon-based material may be selected from at least one of elemental silicon, silicon oxide compounds, silicon-carbon composites, silicon-nitrogen composites, and silicon alloys. The tin-based material may be selected from at least one of elemental tin, tin oxide compounds, and tin alloys.
[0140] In some embodiments, the negative electrode film layer may further include a binder. The binder may be selected from at least one of styrene-butadiene rubber (SBR), polyacrylic acid (PAA), sodium polyacrylate (PAAS), polyacrylamide (PAM), polyvinyl alcohol (PVA), sodium alginate (SA), polymethacrylic acid (PMAA) and carboxymethyl chitosan (CMCS).
[0141] In some embodiments, the negative electrode film layer may further include a conductive agent, which may be selected from at least one of superconducting carbon, acetylene black, carbon black, Ketjen black, carbon dots, carbon nanotubes, graphene and carbon nanofibers.
[0142] In some embodiments, the negative electrode film layer may further include other additives, such as a thickener. For example, the thickener may be sodium carboxymethyl cellulose (CMC-Na).
[0143] In some embodiments, the negative electrode sheet can be prepared in the following manner: the components for preparing the negative electrode sheet, such as the negative electrode active material, the conductive agent, the binder and any other components are dispersed in a solvent such as water to form a negative electrode slurry; the negative electrode slurry is coated on the negative electrode collector, and after drying, cold pressing and other processes, the negative electrode sheet can be obtained.
[0144] Positive electrode
[0145] In a secondary battery, the positive electrode plate generally includes a positive electrode current collector and a positive electrode film layer disposed on the positive electrode current collector, wherein the positive electrode film layer includes a positive electrode active material.
[0146] The positive electrode current collector may be a metal foil or a composite current collector, wherein the composite current collector may be formed by placing a metal material on a polymer substrate. As an example, the positive electrode current collector may be an aluminum foil.
[0147] The specific type of the positive electrode active material can be any active material known in the art that can be used for the positive electrode of a secondary battery, and those skilled in the art can select it according to actual needs.
[0148] As an example, the positive electrode active material may include a lithium ion active material, and the lithium ion active material includes, but is not limited to, one or more of lithium transition metal oxides, lithium-containing phosphates with an olivine structure, and their respective modified compounds. Examples of lithium transition metal oxides may include, but are not limited to, one or more of lithium cobalt oxide, lithium nickel oxide, lithium manganese oxide, lithium nickel cobalt oxide, lithium manganese cobalt oxide, lithium nickel manganese oxide, lithium nickel cobalt manganese oxide, lithium nickel cobalt aluminum oxide, and their modified compounds. Examples of lithium-containing phosphates with an olivine structure may include, but are not limited to, one or more of lithium iron phosphate, a composite material of lithium iron phosphate and carbon, lithium manganese phosphate, a composite material of lithium manganese phosphate and carbon, lithium manganese iron phosphate, a composite material of lithium manganese iron phosphate and carbon, and their modified compounds. These materials can all be obtained through commercial channels.
[0149] As an example, the positive electrode active material may include a sodium ion active material, and the sodium ion active material may employ a positive electrode active material for sodium ion batteries well-known in the art. As an example, the sodium ion active material may include at least one of the following materials: Prussian blue (PBA) type, with the chemical formula (NaxMA[MB(CN)6]·zH2O, where MA and MB are transition metal ions, which is a compound composed of sodium, transition metal, and cyanide, such as Na4Fe2(CN)6, Na4Fe(CN)6, Na 1.72 MnFe2(CN)6, NaMnMn(CN)6, NaNiFe(CN)6, etc.; oxide type, with the chemical formula NaxMO2, 0 < x ≤ 1, where M is a transition metal element, which is composed of transition metal oxides. The variable-valence transition metals involved mainly include vanadium (V), chromium (Cr), manganese (Mn), iron (Fe), cobalt (Co), nickel (Ni), and copper (Cu), among which manganese and iron with relatively rich resources are most commonly used. For example, NaCrO2, NaMnO2, NaMnO2, Na 0.61 Ti 0.48 Mn 0.52 O2, Na[Fe 0.5 Co 0.5 O2, NaMnO2, Na[Ni 0.25 Fe 0.5 Mn 0.25 O2, etc.; and polyanion compound type, with the chemical formula Na x M y [(XO m ) n- z , M is a metal ion with a variable valence state, X is an element such as P, S and V, which is composed of sodium, transition metals and anions, among which the transition metals mainly include iron, vanadium, cobalt, etc., and the anions mainly include phosphate, pyrophosphate, fluorophosphate and sulfate, such as NaMnFe2(PO4)6, Na2MnP2O7, Na3V2(PO4)3, Na2Fe2(SO4)3, NaFePO4, Na3V2(PO4)2F3, Na4Co3(PO4)2(P2O7).
[0150] In some embodiments, the modified compounds of the above materials may be doping-modified and / or surface-coated modified materials.
[0151] It is understandable that the battery will be accompanied by the deintercalation and consumption of active ions such as lithium (Li) during the charging and discharging process, and the content of active ions such as Li in the positive electrode plate is different when the battery is discharged to different states. Taking lithium ion active materials as an example, in the list of positive electrode active materials in this application, unless otherwise specified, the content of Li is the initial state of the material. The positive electrode active material is applied to the positive electrode plate in the battery system, and after the charge and discharge cycle, the content of Li in the positive electrode active material contained in the plate usually changes. Among them, the content of Li can be measured by molar content, but is not limited to this. Regarding "the content of Li is the initial state of the material", the initial state of the material refers to the state before the material is added to the positive electrode slurry. It can be understood that the material obtained by appropriate modification on the basis of the listed positive electrode active materials is also within the scope of the positive electrode material. The aforementioned appropriate modification refers to the acceptable modification method for the positive electrode active material, and non-limiting examples include coating modification.
[0152] In the list of positive electrode active materials in this application, the content of oxygen (O) is only a theoretical state value. The release of oxygen from the lattice will cause the molar content of oxygen to change, and the actual content of oxygen atoms will fluctuate. Among them, the content of oxygen atoms can be measured by molar content, but is not limited to this.
[0153] The positive electrode film layer may also optionally include a binder, a conductive agent and other optional additives.
[0154] As an example, the conductive agent may be one or more of superconducting carbon, acetylene black, carbon black, Ketjen black, carbon dots, carbon nanotubes, Super P (SP), graphene, and carbon nanofibers.
[0155] As an example, the binder can be one or more of styrene-butadiene rubber (SBR), water-based acrylic resin, polyvinylidene fluoride (PVDF), polytetrafluoroethylene (PTFE), ethylene-vinyl acetate copolymer (EVA), polyacrylic acid (PAA), carboxymethyl cellulose (CMC), polyvinyl alcohol (PVA) and polyvinyl butyral (PVB).
[0156] In some embodiments, the positive electrode sheet can be prepared by the following method: the components for preparing the positive electrode sheet, such as the positive electrode active material, the conductive agent, the binder and any other components are dispersed in a solvent to form a positive electrode slurry; the positive electrode slurry is coated on the positive electrode current collector, and the positive electrode sheet can be obtained after drying, cold pressing and other processes. The solvent includes but is not limited to N-methylpyrrolidone.
[0157] Electrolytes
[0158] The electrolyte plays the role of conducting ions between the positive electrode and the negative electrode. For example, the electrolyte can be liquid, gel or all-solid.
[0159] In some embodiments, the electrolyte is an electrolyte solution, which includes an electrolyte salt and a solvent.
[0160] In some embodiments, the electrolyte salt includes at least one of a sodium salt, a lithium salt, and a potassium salt.
[0161] As an example, the sodium salt in the electrolyte salt can be selected from one or more of sodium perchlorate (NaClO4), sodium tetrafluoroborate (NaBF4), sodium hexafluorophosphate (NaPF6), sodium hexafluoroarsenate (NaAsF6), sodium trifluoroacetate (CF3COONa), sodium tetraphenylborate (NaB(C6H5)4), sodium trifluoromethylsulfonate (NaSO3CF3), sodium bis(fluorosulfonyl)imide (Na[(FSO2)2N]) or sodium bis(trifluoromethylsulfonyl)imide (Na[(CF3SO2)2N]).
[0162] As an example, the lithium salt in the electrolyte salt can be selected from one or more of lithium hexafluorophosphate (LiPF6), lithium tetrafluoroborate (LiBF4), lithium perchlorate (LiClO4), lithium hexafluoroarsenate (LiAsF6), lithium bis(fluorosulfonyl)imide (LiFSI), lithium bis(trifluoromethanesulfonyl)imide (LiTFSI), lithium trifluoromethanesulfonate (LiTFS), lithium difluorooxalatoborate (LiDFOB), lithium dioxalatoborate (LiBOB), lithium difluorophosphate (LiPO2F2), lithium difluorobis(oxalatophosphate) (LiDFOP) and lithium tetrafluorooxalatophosphate (LiTFOP).
[0163] In some embodiments, the solvent includes at least one of an ether solvent, an ester solvent and a sulfone solvent.
[0164] As an example, the ether solvent may include at least one of ethylene glycol dimethyl ether (DME), diethylene glycol dimethyl ether (DEGDME), triethylene glycol dimethyl ether (TRGDME), tetraethylene glycol dimethyl ether (TEGDME), and 1,3-dioxolane (DOL);
[0165] As an example, the ester solvent may include at least one of ethylene carbonate (EC), propylene carbonate (PC), butylene carbonate (BC), vinylene carbonate (VC), fluoroethylene carbonate (FEC), ethyl methyl carbonate (EMC), dimethyl carbonate (DMC), diethyl carbonate (DEC), dipropyl carbonate (DPC), methyl propyl carbonate (MPC), ethyl propyl carbonate (EPC), γ-butyrolactone (BL), 1,3-propane sultone (1,3-PS), methyl propionate (MP), methyl butyrate (MB), ethyl acetate (EA), ethyl propionate (EP), propyl propionate (PP) and ethyl butyrate (EB).
[0166] As an example, the sulfone-based solvent includes dimethyl sulfoxide (DMSO).
[0167] In some embodiments, the electrolyte may further include additives, such as negative electrode film-forming additives, positive electrode film-forming additives, and additives that can improve certain battery properties, such as additives that improve battery overcharge performance, additives that improve battery high or low temperature performance, etc.
[0168] Isolation film
[0169] In some embodiments, the secondary battery further includes a separator, which is disposed between the positive electrode sheet and the negative electrode sheet to perform a separation function.
[0170] In some embodiments, the material of the isolation membrane can be selected from at least one of glass fiber, non-woven fabric, polyethylene, polypropylene and polyvinylidene fluoride.
[0171] The isolation film can be a single-layer film or a multi-layer composite film. When the isolation film is a multi-layer composite film, the materials of each layer can be the same or different.
[0172] Unless otherwise specified, the above raw materials can be obtained from the market.
[0173] The shape of the secondary battery in the embodiment of the present application can be cylindrical, square or any other shape. Figure 3 The battery cell 1 is a square structure as an example.
[0174] In some embodiments, reference Figure 4 The outer packaging may include a shell 11 and a cover plate 13. Among them, the shell 11 may include a bottom plate and a side plate connected to the bottom plate, and the bottom plate and the side plate enclose a receiving cavity. The shell 11 has an opening connected to the receiving cavity, and the cover plate 13 can be covered on the opening to close the receiving cavity. The positive electrode sheet, the negative electrode sheet and the isolation membrane can form an electrode assembly 12 through a winding process or a lamination process. The electrode assembly 12 is encapsulated in the receiving cavity. The above-mentioned electrolyte is impregnated in the electrode assembly 12. The number of electrode assemblies 12 contained in the battery cell 1 can be one or more, and those skilled in the art can select according to specific actual needs.
[0175] The secondary battery may be a battery cell, a battery module or a battery pack.
[0176] Figure 5 3 is an example of a battery module. Figure 5 In the battery module 3, the plurality of battery cells 1 may be arranged in sequence along the length direction of the battery module 3. Of course, they may also be arranged in any other manner. Further, the plurality of battery cells 1 may be fixed by fasteners.
[0177] Optionally, the battery module 3 may further include a housing having a receiving space, and the plurality of battery cells 1 are received in the receiving space.
[0178] In some of the embodiments, the battery modules may be assembled into a battery pack. The battery pack may contain one or more battery modules. A person skilled in the art may select a suitable number based on the application and capacity of the battery pack.
[0179] Figure 6 and Figure 7 2 is an example of a battery pack 2. Figure 6 and Figure 7 The battery pack 2 may include a battery box and a plurality of battery modules 3 disposed in the battery box. The battery box includes an upper box body 21 and a lower box body 22. The upper box body 21 can cover the lower box body 22 and form a closed space for accommodating the battery modules 3. The plurality of battery modules 3 can be arranged in the battery box in any manner.
[0180] In addition, the present invention further provides an electrical device, which includes the secondary battery provided by the present invention. The secondary battery can be used as a power source for the electrical device, and can also be used as an energy storage unit for the electrical device. The electrical device may include mobile devices, electric vehicles, electric trains, ships and satellites, energy storage systems, etc., but are not limited thereto. Among them, the mobile device may be, for example, a mobile phone, a laptop computer, etc.; the electric vehicle may be, for example, a pure electric vehicle, a hybrid electric vehicle, a plug-in hybrid electric vehicle, an electric bicycle, an electric scooter, an electric golf cart, an electric truck, etc., but are not limited thereto.
[0181] As the electrical device, a secondary battery can be selected according to its usage requirements.
[0182] Figure 8 The power consumption device 4 is taken as an example. The power consumption device is a pure electric vehicle, a hybrid electric vehicle, or a plug-in hybrid electric vehicle.
[0183] As another example, the device may be a mobile phone, a tablet computer, a laptop computer, etc.
[0184] In order to make the purpose, technical solutions and advantages of the present invention more concise and clear, the present invention is described with the following specific embodiments, but the present invention is by no means limited to these embodiments. The embodiments described below are only preferred embodiments of the present invention, which can be used to describe the present invention and cannot be understood as limiting the scope of the present invention. It should be pointed out that any modifications, equivalent substitutions and improvements made within the spirit and principles of the present invention should be included in the protection scope of the present invention.
[0185] In order to better illustrate the present invention, the present invention is further described below in conjunction with the embodiments. The following are specific embodiments.
[0186] (I) Preparation of negative electrode active materials
[0187] Example 1
[0188] (1) Expanded graphite was added into a mixed acid solution of concentrated nitric acid and concentrated sulfuric acid in a volume ratio of 1:1, and then soaked for 4 hours, and then washed until neutral to obtain oxidized expanded graphite.
[0189] (2) The oxidized expanded graphite is mixed with the carbon source glucose and the nitrogen source pyrrole to form a dispersion, and a hydrothermal reaction is performed at a hydrothermal temperature of 200° C. for 2 h.
[0190] (3) The hydrothermal product is centrifuged, and the precipitate is calcined and decomposed at 500° C. for 4 h in an inert gas atmosphere to form porous carbon on the interlayer surface of the expanded graphite.
[0191] (4) High-purity silane SiH4 is mixed with acetylene and nitrogen in a volume ratio of 1:0.1:1 and sent into a chemical vapor deposition reaction system together. The deposition temperature is controlled to be 800°C and the time is shown in Table 1. The silane penetrates into the pores of the porous carbon of the expanded graphite and completes diffusion and reduction to obtain silicon particles.
[0192] (5) introducing acetylene into the chemical vapor deposition reaction system of step (4), controlling the deposition temperature to 800° C. and the time to 1 h, and carbon-coating the product obtained in step (4) to obtain a negative electrode active material, i.e., a carbon-coated carbon-silicon composite expanded graphite material; wherein the mass content of the carbon coating in the negative electrode active material is 1%.
[0193] The mass content of oxygen-containing groups in the oxidized expanded graphite, the mass ratio of the carbon source to the oxidized expanded graphite, the mass ratio of the nitrogen source to the oxidized expanded graphite in Example 1, the deposition time in step (4), and the parameters of the obtained negative electrode active material are detailed in Table 1.
[0194] It can be understood that the mass content of oxygen-containing groups in the oxidized expanded graphite, the mass ratio of the porous carbon layer to the oxidized expanded graphite, and the mass ratio of the silicon particles to the oxidized expanded graphite can be calculated by the mass changes before and after.
[0195] Other embodiments
[0196] The method is substantially the same as Example 1, except that the preparation parameters and / or the parameters of the negative electrode active material in Table 1 are different.
[0197] It can be understood that the mass content of oxygen-containing groups in the oxidized expanded graphite can be regulated by the immersion time of step (1); the mass ratio A of porous carbon to oxidized expanded graphite and the thickness of the porous carbon layer can be regulated by the mass ratio C of the carbon source to the oxidized expanded graphite; the mass ratio B of silicon particles to oxidized expanded graphite can be regulated by the deposition time of silicon particles formed in step (4); the doping content of nitrogen (relative to porous carbon) can be regulated by the ratio of the added amount of nitrogen source to carbon source (which can be obtained by the mass ratio C of carbon source to oxidized expanded graphite and the mass ratio D of nitrogen source to oxidized expanded graphite).
[0198] Comparative Example 1
[0199] The method is basically the same as Example 1, except that steps (1) to (3) in the example are omitted; that is, steps (4) and (5) are directly carried out using expanded graphite as raw material.
[0200] (II) Battery preparation
[0201] (1) Preparation of positive electrode sheet
[0202] The positive electrode active material ternary material nickel cobalt manganese (NCM 811), conductive agent acetylene black, and binder polyvinylidene fluoride (PVDF) are mixed evenly in a mass ratio of 97:2:1 and added into a solvent NMP to prepare a positive electrode slurry; the positive electrode slurry is evenly coated on the positive electrode collector aluminum foil, dried at 85°C and then cold pressed, and then die-cut and slit to prepare a lithium-ion battery positive electrode sheet.
[0203] (2) Preparation of negative electrode sheet
[0204] Artificial graphite, the negative electrode active material prepared in the above embodiments or comparative examples, conductive agent acetylene black, thickener sodium hydroxymethyl cellulose (CMC), and binder styrene butadiene rubber (SBR) are added to solvent water in a mass ratio of 48:48:2:1:1, mixed evenly and made into a negative electrode slurry; the negative electrode slurry is evenly coated on the negative electrode collector copper foil, dried at 85°C and then cold pressed to make a lithium ion battery negative electrode sheet.
[0205] (3) Preparation of isolation membrane
[0206] A polyethylene microporous film with a thickness of 12 μm is used as a porous isolation membrane substrate. Inorganic alumina powder, polyvinylpyrrolidone, and acetone solvent are evenly mixed in a weight ratio of 3:1.5:5.5 to form an inorganic slurry. The inorganic slurry is coated on both sides of the substrate and dried to form an inorganic layer with a thickness of 5 μm to obtain an isolation membrane.
[0207] (4) Preparation of electrolyte
[0208] Lithium hexafluorophosphate is dissolved in a mixed solvent of ethylene carbonate, dimethyl carbonate and ethyl methyl carbonate (the volume ratio of ethylene carbonate, dimethyl carbonate and ethyl methyl carbonate is 1:2:1) to obtain a lithium ion battery electrolyte. The concentration of lithium hexafluorophosphate is 1 mol / L.
[0209] (5) Preparation of lithium-ion batteries
[0210] The positive electrode sheet, negative electrode sheet and separator are wound to obtain a bare cell, and then the cells are packaged, injected with electrolyte (electrolyte), formed, and vented to obtain lithium-ion batteries. The N / P of the battery is 1, and the battery design rated capacity is 100Ah.
[0211] (III) Electrochemical test
[0212] (1) Cyclic performance test
[0213] The lithium-ion batteries prepared in the above-mentioned embodiments and comparative examples were used as the objects. At 25°C, they were charged to 4.3V at a constant current of 1C, then charged at a constant voltage of 4.3V until the current dropped to 0.05C, and then discharged to 2.5V at a constant current of 1C, and the first-cycle discharge capacity (Cd1) was obtained; this charging and discharging was repeated until the nth cycle, and the discharge capacity after the nth cycle was recorded as Cdn.
[0214] Capacity retention rate = discharge specific capacity after n cycles (Cdn) / first cycle discharge specific capacity (Cd1). The number of cycles corresponding to the capacity retention rate in Table 1 is 500.
[0215] (2) Gram capacity test of negative electrode
[0216] The negative electrode sheets prepared in the above embodiments and comparative examples are used as the object. At 25°C, the negative electrode sheets are made into button batteries and charged to 0.05V at a constant current of 0.1C, then charged to a current of 0.05C at a constant voltage, left to stand for 5 minutes, and then discharged to 2V at a constant current of 0.1C, and the discharge capacity at this time is recorded. The discharge capacity is divided by the total mass of the negative active material in the negative electrode sheet to obtain the 0.1C gram capacity, in units of mAh / g.
[0217] (3) Rate performance test
[0218] Capacity test of secondary batteries
[0219] The lithium-ion batteries prepared in the above-mentioned embodiments and comparative examples were used as the objects. At 25°C, each secondary battery was charged to 4.3V at a constant current of 1C, then charged to a current of 0.05C at a constant voltage, left to stand for 5 minutes, and then discharged to 2.5V at a constant current of 1C. The discharge capacity at this time was recorded, which was the 1C discharge capacity.
[0220] The lithium-ion batteries prepared in the above-mentioned embodiments and comparative examples are used as the objects. At 25°C, the secondary battery is charged to 4.3V at a constant current of 0.33C, then charged to a current of 0.05C at a constant voltage, left to stand for 5 minutes, and then discharged to 2.5V at a constant current of 0.33C, and the discharge capacity at this time is recorded, which is the 0.33C discharge capacity.
[0221] The rate performance of the battery is expressed by 1C / 0.33C(%), where 1C / 0.33C(%)=1C discharge capacity / 0.33C discharge capacity×100%. The larger the value, the better the rate performance.
[0222] Some parameters and battery performance results of the above embodiments and comparative examples are shown in Table 1.
[0223] Table 1
[0224]
[0225]
[0226] In Table 1:
[0227] The mass content of oxygen-containing groups, that is, the mass content of oxygen-containing groups in the oxidized expanded graphite, can be calculated by the mass change before and after performing step (1).
[0228] The mass ratio A, i.e., the mass ratio of porous carbon to oxidized expanded graphite, can be obtained by subtracting the mass of the oxidized expanded graphite used in step (2) from the mass of the product obtained in step (3) to obtain the mass of porous carbon, and then calculating the ratio of the mass of the oxidized expanded graphite to the mass of the oxidized expanded graphite. Wherein, when a nitrogen source is added in step (2), the mass of the porous carbon obtained includes the mass of the doped nitrogen atoms; in this case, the mass ratio of porous carbon to oxidized expanded graphite refers to the mass ratio of nitrogen-doped porous carbon to oxidized expanded graphite.
[0229] The doping content of nitrogen relative to the porous carbon is obtained by subtracting the mass of the oxidized expanded graphite used in step (2) from the mass of the product obtained in step (3), and then testing the mass of nitrogen atoms by elemental analysis and other methods. The ratio of the mass of nitrogen atoms to the mass of the porous carbon is the doping content of nitrogen relative to the porous carbon.
[0230] The thickness of the porous carbon layer is obtained by performing CP slice analysis on the negative electrode active material.
[0231] The BET specific surface area of the porous carbon layer can be measured by the BET specific surface area test method.
[0232] The average pore size of the porous carbon layer is determined by magnifying the surface of the material by microscope photographs, etc., calculating the number of pores per unit length (for example, when the pore size is approximately in the range of 0.1 to 2 nm, the unit length is 10 nm; or when the pore size is approximately in the range of 2 to 40 nm, the unit length is 100 nm) as the number of cells, and then calculating the average pore size by the following equation: Average pore size = unit length / number of cells.
[0233] The mass ratio B, i.e., the mass ratio of silicon particles to oxidized expanded graphite, can be obtained by calculating the mass difference between the product obtained in step (4) and the mass of the oxidized expanded graphite deposited with porous carbon used in step (4), and then calculating the mass of the silicon particles by comparing the mass of the oxidized expanded graphite used.
[0234] In Comparative Example 1, steps (1) to (3) of forming porous carbon on the interlayer surface of the expanded graphite are omitted, and the step (4) of depositing silicon particles and the step (5) of carbon coating are directly performed using the expanded graphite raw material in step (1). The silicon particles are not firmly deposited on the expanded graphite, and it is difficult to achieve a high load of silicon particles. In addition, the disordered filling state of the silicon particles inside the expanded graphite and the uneven grain distribution of the silicon particles will lead to uneven volume distribution of the prepared negative electrode active material during the cycle, and cause uneven distribution and excessive consumption of active lithium, thereby resulting in poor cycle stability and rate performance of the negative electrode active material. In addition, the gram capacity is also low.
[0235] In each embodiment, a porous carbon layer is formed on the interlayer surface of expanded graphite in advance, and then silicon particles are deposited in the pores of the porous carbon in the porous carbon layer. The pores of the porous carbon provide storage space for the uniform deposition of silicon particles, so that the silicon particles can be evenly dispersed between the layers of the expanded graphite, which is not only conducive to the high load of silicon particles, but also the lamellar structure of the expanded graphite is conducive to the structural enhancement and conductivity improvement of the internal negative electrode active material, and also provides space for the expansion of silicon particles during the cycle, thereby improving its stability and rate performance during the cycle.
[0236] Comparing Examples 1 to 5, it can be seen that the total amount of negative electrode active materials in Example 2 is relatively small, so its gram capacity is relatively low. Comparing the mass of porous carbon and silicon particles in Example 4, it can be seen that the mass of silicon particles is much greater than the mass of porous carbon, so in addition to being deposited in the pores of porous carbon, some silicon particles are also deposited on the surface of porous carbon, which reduces its cycle retention rate and rate performance to a certain extent.
[0237] By comparing Examples 6 to 9, it can be seen that the difference is that the amount of nitrogen source added during the preparation process is different. When the amount of expanded graphite added is unchanged, the mass ratio of the nitrogen source to the expanded graphite as shown in Table 1 is different, so that the nitrogen doping content relative to the porous carbon in the prepared negative electrode active material is different; among them, the amount of nitrogen source added in Example 9 is 0, and the cycle retention rate and rate performance of the battery are relatively low.
[0238] In Examples 10 to 11, the mass of the silicon particles in Example 10 is much greater than the mass of the porous carbon. Therefore, in addition to being deposited in the pores of the porous carbon, some of the silicon particles are also deposited on the surface of the porous carbon, thereby reducing its cycle retention rate and rate performance to a certain extent.
[0239] Compared with Example 1, the difference of Example 12 is that the expanded graphite is not subjected to the oxidation treatment of step (1), and steps (2) to (5) are directly performed. Therefore, the porous carbon deposited on the expanded graphite is not firm. As the battery is charged and discharged multiple times, the stability of the negative electrode active material decreases, thereby reducing the cycle performance of the battery.
[0240] The technical features of the above-described embodiments may be arbitrarily combined. To make the description concise, not all possible combinations of the technical features in the above-described embodiments are described. However, as long as there is no contradiction in the combination of these technical features, they should be considered to be within the scope of this specification.
[0241] The above-mentioned embodiments only express several implementation methods of the present invention, and the description thereof is relatively specific and detailed, but it cannot be understood as limiting the scope of the invention patent. It should be pointed out that for ordinary technicians in this field, several variations and improvements can be made without departing from the concept of the present invention, which all belong to the protection scope of the present invention. Therefore, the protection scope of the patent of the present invention shall be based on the attached claims, and the description and drawings can be used to interpret the content of the claims.
Claims
1. A negative electrode active material, characterized in that: The invention comprises expanded graphite, a porous carbon layer and silicon particles. The expanded graphite comprises a plurality of graphite layers. The porous carbon layer is at least distributed on the interlayer surface of one of the graphite layers. The silicon particles are at least distributed in the porous carbon pores of the porous carbon layer.
2. The negative electrode active material according to claim 1, characterized in that The porous carbon layer covers the surface of at least one of the graphite layers; optionally, the porous carbon layer covers the surface of each of the graphite layers.
3. The negative electrode active material according to claim 1, characterized in that The expanded graphite is oxidized expanded graphite; Optionally, the oxygen-containing groups in the expanded graphite include at least one of hydroxyl groups, epoxy groups and carboxyl groups.
4. The negative electrode active material according to claim 1, characterized in that At least one of the following conditions is met: (1a) The mass ratio of the porous carbon layer to the expanded graphite is (0.1-20):1, and can be optionally (4-16):1; (1b) The thickness of the porous carbon layer is 0.05 to 20 μm, and can be 0.2 to 10 μm; (1c) The BET specific surface area of the porous carbon layer is 40 to 1500 m 2 / g, optional: 600~1500m 2 / g; (1d) The average pore size of the porous carbon layer is 0.1 to 40 nm; (1e) The porous carbon layer is doped with nitrogen atoms; optionally, the mass content of the nitrogen atoms relative to the porous carbon layer is 0.1% to 20%.
5. The negative electrode active material according to any one of claims 1 to 4, characterized in that At least one of the following conditions is met: (2a) The mass ratio of the silicon particles to the expanded graphite is (0.08-20):1, and can be optionally (3-18):1; (2b) The macroscopic average particle size of the silicon particles is 0.05 nm to 30 nm; (2c) The mass ratio of the silicon particles to the porous carbon layer is (0.7-12):1, and can be (0.7-1.5):1; (2d) In the negative electrode active material, the mass content of the silicon particles is 6% to 65%.
6. The negative electrode active material according to any one of claims 1 to 4, characterized in that The negative electrode active material further includes a coating layer, and the coating layer is coated on at least a portion of the outer surface of the expanded graphite; Optionally, the coating layer comprises a carbon material; Optionally, the mass content of the coating layer in the negative electrode active material is 0.2% to 3%; Optionally, the coating layer has a thickness of 0.5 to 200 nm.
7. The method for preparing a negative electrode active material according to any one of claims 1 to 6, characterized in that: The steps include: Mixing expanded graphite with a carbon source solution and performing a hydrothermal reaction, and then calcining a solid product of the hydrothermal reaction to obtain an intermediate product; the intermediate product includes expanded graphite and a porous carbon layer distributed on the surface of a graphite layer in the expanded graphite; and Silicon particles are formed in the pores of the porous carbon of the intermediate product.
8. The method for preparing the negative electrode active material according to claim 7, characterized in that: At least one of the following conditions is met: (3a) the carbon source in the carbon source solution comprises at least one of glucose, asphalt, sucrose and phenolic resin; (3b) the mass ratio of the carbon source in the carbon source solution to the expanded graphite is (1-200):1; (3c) A nitrogen source is further added to the hydrothermal reaction; optionally, the nitrogen source comprises at least one of pyrrole, melamine and acetonitrile; (3d) the hydrothermal reaction temperature is 80 to 280° C. and the time is 0.5 to 5 h; (3e) The calcination conditions include: calcining at 400-1000° C. for 1-5 hours; (3f) The expanded graphite is oxidized expanded graphite; optionally, the oxygen-containing groups in the expanded graphite include at least one of hydroxyl groups, epoxy groups and carboxyl groups; optionally, the mass content of the oxygen-containing groups in the expanded graphite is 0.5% to 38%.
9. The method for preparing the negative electrode active material according to claim 7, characterized in that: The step of forming silicon particles in the pores of the porous carbon of the intermediate product comprises the following steps: Passing silane and reducing gas into the intermediate product, and performing chemical vapor deposition under a protective atmosphere; Optionally, the silane includes at least one of monosilane and disilane; Optionally, the temperature of the chemical vapor deposition is 400-1000° C.; Optionally, the chemical vapor deposition time is 1 to 5 hours.
10. The method for preparing the negative electrode active material according to claim 9, characterized in that: Passing a gas raw material into the product obtained by chemical vapor deposition to perform chemical vapor deposition, wherein the gas raw material includes at least one of ethylene, acetylene and propylene; Optionally, the temperature of the chemical vapor deposition is 600-1200° C.; Optionally, the chemical vapor deposition time is 1 to 5 hours.
11. The method for preparing a negative electrode active material according to any one of claims 7 to 10, characterized in that: The expanded graphite is oxidized expanded graphite; the preparation method further comprises the steps of preparing the oxidized expanded graphite, comprising the following steps: After the expanded graphite is soaked in an acid solution and washed to neutrality, oxidized expanded graphite is obtained; Optionally, the acid solution includes at least one of HNO3 and H2SO4.
12. A negative electrode plate, characterized in that: The negative electrode sheet comprises the negative electrode active material according to any one of claims 1 to 6.
13. A secondary battery, characterized in that: Comprising the negative electrode sheet as described in claim 12.
14. An electrical device, characterized in that: Comprising the secondary battery as claimed in claim 13.
Citation Information
Patent Citations
Preparation method of high power capacity lithium ion battery cathode material
CN102769139A
Hard carbon coated expanded microcrystalline graphite material as well as preparation method and application thereof in sodium ion battery
CN109616639A
Silicon monoxide / expanded graphite / carbon composite material and preparation method thereof
CN114744167A
Preparation method of three-dimensional composite silicon-carbon negative electrode material
CN115483385A
Negative active material having expanded graphite and silicon fusions for lithium secondary battery, method for preparing the same and lithium secondary battery comprising thereof
KR101855848B1
Cited By
Negative electrode active material and preparation method therefor, negative electrode sheet, secondary battery, and device
EP4629327A1
Negative electrode active material and preparation method therefor, negative electrode sheet, secondary battery, and device
WO2025020287A1